Update on The Risk Factors and Treatment Options for Rheumatoid Arthritis - Chen, Pengyu; Gan, Yicheng; Lin, Jingxue; Zhao, Wanxin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Rheumatoid arthritis (RA) is characterized by inflammation of the surrounding joints and tissue hyperplasia, which affect all joints in the body. Although RA is generally not fatal, extrarthral lesions may have adverse consequences, which should be paid enough attention to. At present, the treatment mainly relies on anti-inflammatory, analgesic and immunosuppressive drugs, but the problems of relapse and the adverse drug reactions are still faced. This paper introduces the different high-risk factors of the disease, and the related drug and non-drug intervention measures. At the same time, it expounds the new targets of current treatment, such as psychological intervention, exercise intervention, diet intervention, traditional Chinese medicine intervention, and non-drug intervention assisted by digital remote monitoring. To further reduce the disease progression of RA, and to provide reference for improving the life quality and carrying out continuous care, the problems of the intervention methods were summarized and the prospects for future research were put forward.